Modulation of dopamine release from rat striatum by protein kinase C: interaction with presynaptic D(2)-dopamine-autoreceptors - Iannazzo, L (1997)
1. Interactions between dopamine receptors and protein kinase C (PKC) have been proposed from biochemical studies. The aim of the present study was to investigate the hypothesis that there is an interaction between protein kinase C and inhibitory D(2)-dopamine receptors in the modulation of stimulation-induced (S-I) dopamine release from rat striatal slices incubated with [(3)H]-dopamine. Dopamine release can be modulated by protein kinase C and inhibitory presynaptic D(2) receptors since phorbol dibutyrate (PDB) and (−)-sulpiride, respectively, elevated S-I dopamine release. 2. The protein kinase C inhibitors polymyxin B (21 μM) and chelerythrine (3 μM) had no effect on stimulation-induced (S-I) dopamine release. However, when presynaptic dopamine D(2) receptors were blocked by sulpiride (1 μM), an inhibitory effect of both PKC inhibitors on S-I dopamine release was revealed. Thus, sulpiride unmasks an endogenous PKC effect on dopamine release which suggests that presynaptic D(2) receptors normally suppress endogenous PKC activity. This is supported by results in striatal slices which were pretreated with PDB to down-regulate PKC. In this case the facilitatory effect of sulpiride was completely abolished. 3. The inhibitory effect of the dopamine D(2)/D(3) agonist quinpirole on S-I dopamine release was partially attenuated by PKC down-regulation. Since the effect of sulpiride was completely abolished under the same conditions, this suggests that exogenous agonists may target a PKC-dependent as well as a PKC-independent pathway. The inhibitory effect of apomorphine was not affected by either polymyxin B or PKC down-regulation, suggesting that it operated exclusively through a PKC-independent mechanism. 4. These results suggest that there are at least two pathways involved in the inhibition of dopamine release through dopamine receptors. One pathway involves dopamine receptor suppression of protein kinase C activity, perhaps through inhibition of phospholipase C activity and this is preferentially utilized by neuronally-released dopamine. The other pathway which seems to be utilized by exogenous agonists does not involve PKC.